Muscle oxygen saturation plateau: Definition and verification in different oxygen availability conditions in locomotor and non-locomotor muscles - Kowalski, T.; Rebis, K.; Wilk, A.; Granda, D.; Bialecki, A.; Debevec, T.; Faiss, R. (Experimental Physiology, 2026)
Novel wearable near-infrared spectroscopy devices allow for a better understanding of muscle oxygenation kinetics during exercise. A muscle oxygen saturation (SmO2) plateau is often applied in the scientific literature, but clear criteria for its definition remain unestablished to date. The aim of this study was to develop criteria allowing for definition of SmO2 plateaus. Multiple variables associated with physiological plateaus during exercise were assessed to develop a framework for an SmO2 plateau. Subsequently, the existence of an SmO2 plateau during 3 min all-out cycling trials (critical oxygenation plateau) was tested in different conditions of oxygen availability (i.e., normoxia and hypoxia) in vastus lateralis and triceps brachii among 30 endurance athletes. Plateau determination methods based on a threshold of change of ±5 arbitrary units (a.u.) of SmO2 and expert visual assessment showed almost perfect agreement. However, a threshold of 10 a.u. yielded high SmO2 variability associated with a large number of possibly false-positive detections. Conversely, relative changes (thresholds of 5% and 10%) did not align with other methods, corresponding to low absolute changes, limiting their applicability. The inter-rater agreement between individual visual assessments exhibited a higher reliability among expert versus non-expert raters. The determination of an SmO2 plateau depends on the applied methodology. Overall, a critical oxygenation plateau was observed in the vastus lateralis in both normoxia and hypoxia in >90% of cases. The results of this study allow recommendation either for the use of a threshold of change corresponding to 5 a.u. of SmO2 or expert visual assessment, using 30 s segments.